1997
DOI: 10.1002/hep.510250143
|View full text |Cite
|
Sign up to set email alerts
|

Nucleic Acid Sequence Analysis of the Precore Region of Hepatitis B Virus From Sera of Southern African Black Adult Carriers of the Virus

Abstract: an indicator of active viral replication and high levels of infecOur purpose was to ascertain if mutations of the pretivity. HBeAg negativity and hepatitis B e antigen antibody core region of the hepatitis B virus genome, in particular (anti-HBe) positivity are used as markers of decreased viral the 1896 stop codon mutation, are responsible for the replication and resolution of inflammation. 3 Precore muta-95% hepatitis B e antigen (HBeAg)-negativity rate in tions that abolish HBeAg expression without a concom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
48
0

Year Published

1999
1999
2006
2006

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(51 citation statements)
references
References 58 publications
(5 reference statements)
3
48
0
Order By: Relevance
“…The precore region in Southern African isolates of HBV, studied previously in the same sera, 8,9 showed significantly less nucleotide and amino acid divergence than did the BCP. This was true in both ASCs and patients with HCC.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…The precore region in Southern African isolates of HBV, studied previously in the same sera, 8,9 showed significantly less nucleotide and amino acid divergence than did the BCP. This was true in both ASCs and patients with HCC.…”
Section: Discussionmentioning
confidence: 64%
“…Nucleotide sequencing of the precore region of HBV isolates from a number of countries has shown the 1896 stop codon mutation to be a frequent cause of the HBeAgnegative phenotype, 5,6 with other nonsense or frame-shift mutations accounting for a small proportion (reviewed in Miyakawa et al 7 ). However, these mutations are seldom present in black African carriers in Southern Africa 8,9 and our focus has shifted to the X open reading frame.…”
mentioning
confidence: 99%
“…Infection with HBV/Aa is associated with low prevalence of HBeAg in serum and early seroconversion (14,15). Recently Ahn and coworkers showed that the T1809/T1812 mutations interfere with the translation of HBeAg in vitro and may be responsible for the early loss of HBeAg seen in southern African black carriers of HBV (1).…”
Section: Discussionmentioning
confidence: 99%
“…This subtype has also been found in HBV isolates from Malawi (29). In African countries, genotype A isolates, most of which are subtype AЈ, seem to be associated with low levels of HBV DNA in serum and a low prevalence of hepatitis B e antigen (HBeAg) in serum (14,15). On the other hand, HBV carriers infected with isolates belonging to the remainder of genotype A, distributed widely in European countries and the United States, have a higher rate of sustained remission after seroconversion and a lower rate of death related to liver disease than other genotypes during long-term follow-up (8,24,33).…”
mentioning
confidence: 88%
“…In this regard, a G1862T substitution is frequently detected in patients following seroconversion to anti-HBe (14,33). This point mutation converts residue 17 of the precore peptide, the Ϫ3 position of the signal peptidase cleavage site, to phenylalanine.…”
mentioning
confidence: 99%